2022
DOI: 10.1039/d2cp01828d
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the structure of aqueous magnesium nitrate solutions by combining X-ray diffraction and theoretical calculations

Abstract: The structure of aqueous magnesium nitrate solution is gaining significant interest among researchers, especially whether contact ion pairs exist in concentrated solutions. Here, combining X-ray diffraction experiments, quantum chemical calculations...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…A combined total scattering and computational modelling study was recently reported by Wang and coworkers and this did use an atomistic model to look at the structure of magnesium nitrate and we will compare some of our results to theirs. 25 A similar study was also conducted by Jensen and coworkers looking at amorphous magnesium/calcium carbonates. 26 In the wider context of clustering in solution Sva ¨rd and coworkers 27 have reported impressive studies of molecular systems (fenoxycarb) using a whole barrage of techniques from dynamic light scattering and small angle X-ray scattering to molecular dynamics simulations looking at the molecular clustering in isopropanol solutions.…”
Section: Magnesium Sulfate In Aqueous Solutionmentioning
confidence: 73%
See 4 more Smart Citations
“…A combined total scattering and computational modelling study was recently reported by Wang and coworkers and this did use an atomistic model to look at the structure of magnesium nitrate and we will compare some of our results to theirs. 25 A similar study was also conducted by Jensen and coworkers looking at amorphous magnesium/calcium carbonates. 26 In the wider context of clustering in solution Sva ¨rd and coworkers 27 have reported impressive studies of molecular systems (fenoxycarb) using a whole barrage of techniques from dynamic light scattering and small angle X-ray scattering to molecular dynamics simulations looking at the molecular clustering in isopropanol solutions.…”
Section: Magnesium Sulfate In Aqueous Solutionmentioning
confidence: 73%
“…The missing 5% are fragments based on higher numbers of coordinated sulfates. distance of 2.1 Å), 25 and the second broader feature describing either far-side sulfate oxygens (O1) or a second solvation shell in the case of water (Ow) with distances in the range 4.20-4.35 Å. In both cases the shorter distances have a narrower distribution possibly providing evidence of contact ion pairing (CIP), as described by Zhang and co-workers.…”
Section: Magnesium Environmentmentioning
confidence: 78%
See 3 more Smart Citations